Determinants of the choice leasing vs bank loan: Evidence from the French SME by KACM - Marie Christine Filareto-Deghaye; Eric Severin (Colegio de Economistas de A Coru\~na, 2007)
The question of leasing credit as a substitute or complement of a banking loan has still not been resolved in the financial literature. As a continuation of these arguments, the objective of this article is, on the one hand, to determine the characteristics of firms using leasing credit and on the other hand, to better understand the relationship between leasing and credit rationing. Firstly, our results suggest that SME use leasing all the more the leasing so when they are young, leveraged, less solvent and that they present an small size and an important failure probability. Thus, leasing pushes back the limits of banking debt for firms that have no access to it. Secondly, our results suggest a strong and significant relationship between credit rationing and the use of leasing. In this framework the latter appears to be a last resort financing.
Keywords: 330; Klein- und Mittelunternehmen; Unternehmensfinanzierung; Finanzierungsleasing; Kredit; Kreditrationierung; Frankreich